Effect of dietary enrichment with antioxidants on the sensory quality of raw and cooked Atlantic salmon (Salmo salar L.) - Adhikari, Pradip (Norwegian University of Life Sciences, Ås, 2016)
The main sensory quality parameters of Atlantic salmon are color, texture, fillet integrity, taste and odor. The aim of the present study was to investigate the effect of diet on sensory quality of raw salmon fillets, and sensory quality and consumer acceptability of cooked salmon fillets. Diets investigated were a standard commercial feed and the same feed added antioxidants (vitamin C, vitamin E and selenium). The experiment was carried out from 7th January to 13th March 2015. Salmon with an average body weight of 4123 ± 106 g and 4203 ± 108 g of control and antioxidant diet groups respectively were killed by percussive stunning. Fillet color, gaping and texture were analyzed in the raw fillets after 7 days of ice storage. Untrained assessors evaluated color, odor, tastiness, juiciness, firmness and acceptability of cooked fillets after 7 months of storage at -40°C. The result showed significant higher fillet weight, lower gaping and higher juiciness of salmon fed the antioxidant diet group compared to the control diet. Also a tendency to improved tastiness and firmness were observed for salmon fed the antioxidant diet. Females rated the cooked salmon as tastier, firmer and juicier than males. Color, odor, tastiness and juiciness, but not firmness, correlated significantly to the acceptability. It is concluded from the present experiment that dietary supplementation of antioxidants improved muscle growth, integrity of raw fillets and sensory quality of cooked fillets. M-AA